DYNAMIC CRUSHING PERFORMANCE ANALYSIS FOR AUXETIC HONEYCOMB STRUCTURE - HOU XiuHui; YIN GuanSheng (Jixie qiangdu)
The in-plane dynamic crushing behavior of a new honeycomb structure-the multi-re-entrant honeycomb and reentrant honeycomb topology possessing negative Poisson’s ratio was analyzed here. Firstly the finite element method of ANSYS /LS-DYNA was applied to examine the deformation modes of multi-re-entrant honeycomb and re-entrant honeycomb under different impact loads,where the physical mechanism for the auxetic effect on improving the dynamic crushing strength is revealed. Then the empirical formula of the dynamic crushing strength was deduced based on the classical theory model,where comparisons with the finite element results revealed the effectiveness of the proposed empirical formula. Higher dynamic crushing strength reveals that the re-entrant honeycomb possesses better energy absorption ability than conventional hexagon topology due to its antitraditional deformation mechanism.